Investigation of the recent Earth's crust deformations in the territory of Lithuania - Zakarevičius, Algimantas; Stanionis, Arminas; Levinskaitė, Daiva (Geodesy and Cartography, 2012)
The paper discusses the horizontal movements of the Earth's crust in the territory of Lithuania. The curves of horizontal deformations are found by comparing the changes in coordinates of geodetic network points obtained after repeated measurements carried out after a certain period of time. The goal of the investigation was to analyse the regularities of indications of horizontal movements of the Earth's crust established according to the data of three different geodetic measurements. The parameters of horizontal movements were calculated using the method of finite elements and applying tensor analysis. To implement the investigation in the territory of Lithuania, the authors used the points of the triangulation network, formed in the year 1942; and the points of GPS networks of zero class and first class, formed in the year 1993, and measured once again in the year 2007 (the total of 45 joint points). After the investigation, new curves of horizontal deformations (such as relative linear deformations, relative shear deformations, relative dilatation, the maximum and the minimum elongation of the key horizontal deformations, and the directions of the maximum elongation) were found. In case of the analysis of obtained results, it was found that the positive values of deformations predominate in the direction of the maximum related elongation and the negative values of deformations predominate in the direction of the minimum related elongation. The maximum elongation of the key horizontal deformations varies between −1.608 ·10−6 and 20.832 ·10−6. The minimum elongation of the key horizontal deformations varies between –29.424 ·10−6 and 1.397 ·10−6. Dilatation varies between −27.580 ·10−6 and −8.612 ·10−6. It was found that more intensive changes of indications of deformations were observed at the boundaries of deep blocks of the lithosphere.